Concepts Of Sense of Humanity in Literary Translations (Eurasian Journal of Learning and Academic Teaching, 2022)
In Uzbek literature, which has a long and rich history, and in fascinating works of art created by its leading representatives, portraits of people and their images are portrayed with a unique artistic style and aesthetic taste. Until one thousand nine hundred and seventeen, poetry in Uzbek literature developed and flourished. High works of art were created in various genres, which, like a worthy pearl, entered the treasury of world literature and culture